(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and objectives: Prostaglandins (PGs) are established to have massive effects on different physiological activities. The present study is aimed to analyze the microscopic effects of prostaglandins treated granulosa cells in the caprine antral follicles. Methods: The healthy, slightly atretic and atretic antral follicles of diameter ranging from 3-8 mm in diameter were cultured with prostaglandin E2 (1.0 μg/ml) and prostaglandin F2α (1.0 μg/ml) along with control for 24 hours. The light microscopy for histological preparation to study variations in different categories of follicles was done; ultrastructural details of these categories of cells were studied; and fluorescence microscopy of atretogenic and non atretogenic cells were performed. Results: Histologically, three categories of follicles viz. healthy, slighty atretic having loose granulosa cells and weak cellular compactness and atretic characterized by loose free floating pyknotic granulosa cells and disintegrating follicular structure were observed. The ultrastructure of PGE2 treated and control granulosa cells were almost similar in fine morphology. The healthy, slightly atretic and atretic antral follicles from control and PGE2 group revealed granulosa cells with intact structural integrity and proper intercellular interactions, while PGF2α treated antral follicles showed granulosa cells with vacuolization and electron-dense homogenous osmophillic lipid droplets in cytoplasm, marginated and condensed chromatin along the inner nuclear membrane, and degenerated cell organelles with ruffled outer membrane. Fluorescent images of comets observed in the granulosa cells, statistical evaluation of olive moments and graphical representation of comets were analysed and demonstrated a significant increase in percentage of apoptosis after PGF2α exposure (p < 0.01) both between and within the healthy, slightly atretic and atretic groups, while PGE2 showed a significant (p < 0.01) decrease in percentage of apoptosis as compared to PGF2α and non-significant (p > 0.01) difference with respect to control. Conclusion: Transmission electron microscopy and comet assay revealed that PGE2 has induced positive, while PGF2α induced degenerative changes in the fine morphology of granulosa cells. The present investigation depicted that granulosa cell viability in vitro is influenced by the supply of survival and growth factors and prostaglandin of E series is crucial in the suppression of granulosa cell apoptosis and success of follicular growth, while of F series induces apoptosis and leads to atresia.